Comparative Morbidity Profile of Elective vs Therapeutic Neck Dissection. (20th April 2021) - Dunlap, Quinn; Gardner, James Reed; Ederle, Amanda; King, Deanne; Merriweather, Maya; Vural, Emre; Moreno, Mauricio Alejandro
Abstract : Objective: Neck dissection (ND) is one of the most commonly performed procedures in head and neck surgery. We sought to compare the morbidity of elective ND (END) versus therapeutic ND (TND). Study Design: Retrospective chart review. Setting: Academic tertiary care center. Methods: Retrospective chart review of 373 NDs performed from January 2015 to December 2018. Patients with radical ND or inadequate chart documentation were excluded. Demographics, clinicopathologic data, complications, and sacrificed structures during ND were retrieved. Statistical analysis was performed with χ 2 and analysis of variance for comparison of categorical and continuous variables, respectively, with statistical alpha set a 0.05. Results: Patients examined consisted of 224 males (60%) with a mean age of 60 years. TND accounted for 79% (n = 296) as compared with 21% (n = 77) for END. Other than a significantly higher history of radiation (37% vs 7%, P <. 001) and endocrine pathology (34% vs 2.6%, P <. 001) in the TND group, no significant differences in demographics were found between the therapeutic and elective groups. A significantly higher rate of structure sacrifice and extranodal extension within the TND group was noted to hold in overall and subgroup comparisons. No significant difference in rate of surgical complications was appreciated between groups in overall or subgroup analysis. Conclusion: While the significantly higher rate of structure sacrifice among the TND population represents an increased morbidity profile in these patients, no significant difference was found in the rate of surgical complications between groups. The significant difference seen between groups regarding history of radiation and endocrine pathology likely represents selection bias.